Desarrollo y caracterización de sistemas micro y nanoestructurados como estrategia para la vehiculización de ácido ursodesoxicólico aplicados a la farmacoterapia pediátrica - Boscolo, Oriana (2019)
At present, the lack of formulations to attend the needs of pediatric patients is a frequent problem. This is the case of ursodeoxycholic acid (UDCA) which is available in tablets and capsules, but UDCA administration is erratic and inefficient. This leads to an orphan therapeutics, where liquid pharmaceutical forms are recommended for administration, in order to reduce errors in dosage and help treatment adherence. In this thesis different UDCA oral liquid formulations were developed for the treatment of cholestatic liver diseases. UDCA suspensions suitable for diabetic patients were prepared and characterized chemically and microbiologically and relative bioavailability studies were performed. The suspensions were stable at 25°C and 4°C for at least 4 months and at 40°C for 3 months and presented a similar relative oral bioavailability, both of them improved compared to the tablet. To determine UDCA content and related substances, HPLC-UV and HPLC-MS/MS methods were developed, optimized and validated, which turned out to be simple, fast, accurate, precise and sensitive. Another strategy consisted of the formulation and characterization of an optimal UDCA nanosuspension using the precipitation-ultrasonication method followed by lyophilization. It was chemically characterized, being stable at 25 ° C and 4 ° C for at least 2 months.